USING VIDEO MATERIALS - To‘raqulova Sobira; Toshmirzayeva Sitora; Sattorova Sabohat (TADQIQOTLAR, 2025)
Annotation This paper examines the purposeful application of video content in teaching English to intermediate (B1) learners, focusing on its instructional benefits, classroom implementation techniques, and real-life usage. It outlines how video enhances learner involvement, promotes better contextual and cultural understanding, and boosts listening abilities. The article also presents educators with practical methods for selecting suitable videos, creating engaging tasks, and sustaining student motivation. Aimed at English teachers, this resource supports the integration of multimedia tools to develop communication skills and learner independence.